The prevalence of neutralizing antibodies against adeno‐associated virus capsids is reduced in young Japanese individuals. Issue 11 (17th October 2013) - Mimuro, Jun; Mizukami, Hiroaki; Shima, Midori; Matsushita, Tadashi; Taki, Masashi; Muto, Shinji; Higasa, Satoshi; Sakai, Michio; Ohmori, Tsukasa; Madoiwa, Seiji; Ozawa, Keiya; Sakata, Yoichi
Abstract Pre‐existing antibodies against adeno‐associated virus (AAV), caused by natural AAV infections, interfere with recombinant AAV vector‐mediated gene transfer. We studied the prevalence of neutralizing antibodies against AAV serotypes 1, 2, 5, 8, and 9 in healthy subjects (n = 85) and hemophilia patients (n = 59) in a Japanese population. For healthy subjects, the prevalence of neutralizing antibodies against AAV serotypes 1, 2, 5, 8, and 9 was 36.5%, 35.3%, 37.6%, 32.9%, and 36.5%, respectively, while that in hemophilia patients was 39.7%, 28.8%, 35.6%, 32.9%, and 27.4%, respectively. There was no difference in the prevalence of neutralizing antibody against each AAV serotype between the healthy subjects and the hemophilia patients. The prevalence of neutralizing antibodies against all AAV serotypes increased with age in both healthy subjects and hemophilia patients. High titers of neutralizing antibodies against AAV2 (≥1:224) and AAV8 (≥1:224) were more evident in older individuals (≥42 years old). Approximately 50% of all screened individuals were seronegative for neutralizing antibodies against each AAV tested, while approximately 25% of individuals were seropositive for each AAV serotype tested. The prevalence of seronegativity for all AAV serotypes was 67.0% (healthy subjects, 68.6%; hemophilia patients, 65.0%) and 18.6% (healthy subjects, 20.5%; hemophilia patients, 15.7%) in young (<42 years old) and older subjects (≥42 years old), respectively. The findings from this study suggested that young subjects are more likely to be eligible for gene therapy based on AAV vectors delivered via an intravascular route because of the low prevalence of antibodies to AAV capsids. J. Med. Virol. 86:1990–1997, 2014. © 2013 Wiley Periodicals, Inc.